The osteopathic treatment of somatic dysfunction causing gait abnormality in 51 horses. (16th January 2014) - Colles, C. M.; Nevin, A.; Brooks, J.
Summary Over a 19‐year period, 51 horses showing chronic lameness or gait abnormality that was not fully responsive to veterinary treatment at other referral clinics were referred to us for further treatment. All had either failed to have a diagnosis made, or treatment for the diagnosed conditions had shown only partial response. After further examination, we concluded that they showed abnormal function of the neck or back, but there was no obvious pathological cause. A diagnosis of 'somatic dysfunction' was made, characterised by altered muscle tone, tenderness or subtle changes in gait, similar to the condition recognised in human medicine. These cases subsequently underwent osteopathic treatment under sedation. Forty‐six cases (90.2%) responded to treatment in the short term (6 months after treatment). Seventeen (53.1%) were working at the same level or better than previously at least a year after treatment. Ten (31.2%) worked at a reduced level for between 1.5 and 10 years. Nineteen cases were lost to long‐term follow‐up. The findings of this study suggest that neck and back problems may be overlooked when investigating chronic lameness. When no pathology can be pinpointed as a cause of lameness, a diagnosis of somatic dysfunction as a primary problem should be considered. The presence of somatic dysfunction as a secondary complicating factor should not be overlooked. Stiffness and/or low grade pain in the spine of horses can result in persistent abnormal posture, gait, or behaviour, similar to 'somatic dysfunction' seen in the human patient. The cause is neuromuscular in origin, rather than resulting from tissue pathology. The diagnosis made clinically can be confirmed with thermography. This study confirms that osteopathic manipulation of the spine of horses can be a valuable treatment for cases of lameness that do not respond fully to standard veterinary treatments.